Evaluating X-efficiency and Financial Performance of Chinese banks: A comparative analysis of different types of banks - Han, Xingyu (2019)
With stochastic frontier estimator, using data of 183 banks in China during 2013 and 2018, this study first examines and compares the X-efficiency of commercial banks with three types of ownership, namely state-owned banks, joint-stock banks and other banks (including urban and rural commercial banks and foreign banks). A steady increase trend can be seen in the X-efficiency of the overall banking sector. State-owned and joint-stock banks were less efficient than other banks but surpassed them in the recent two years. Then this study analyzes how the financial ratios affect their profitability with generalized method of moments for the overall banks and other banks to solve endogenous problems and ridge regression for state-owned banks and joint-stock banks to solve problems of multicollinearity. The results express that the profitability of all types of banks are obviously impacted by bank size, capitalization and capital adequacy. In addition, the state-owned banks are also significantly influenced by their liquidity and earning quality. The management efficiency could positively affect both joint-stock banks and other banks. Besides, the asset quality and off-balance sheet income ratio are the other two significant determinants of other-bank profitability. However, there is no evidence that X-efficiency and Z-score of banks affect profitability importantly. The results denote increasing management costs, inadequate capital, and relatively competitive and diversified financial market of Chinese banking sector.